(untitled) (International journal of artificial intelligence, 2025)
This study analyzes the role of digital transformation in collaborative learning between KSU and YKSG, with a focus on integrating information and communication technologies (ICT) and intercultural approaches to form professional competencies of future teachers. An experiment involving 120 students showed that using ICT (Google Workspace, Canva, Moodle) combined with intercultural modules (case studies, role-playing games) significantly enhances general professional (communication, leadership) and specific (teaching methods) competencies, and also reduces psychological barriers, such as stress from intercultural interaction. The results highlight the potential of digital tools in the globalization of pedagogical education and offer recommendations for their integration into international teacher training programs.